Expression of Chicken Leukocyte Cell-Derived Chemotaxin 2 in the Embryonic Bursa of Fabricius - Felfoldi, Balazs; Wang, Hui; Nuthalapati, Nikhil; Taylor, Jr., Robert L.; Evans, Jeffrey D.; Branton, Scott L.; Pharr , Gregory T. (International Journal of Poultry Science, 2020)
Background and Objective: A previous transcriptomics analysis identified the expression of a pleiotropic cytokine, termed leukocyte cell-derived chemotaxin 2 (LECT2) in the bursa of Fabricius of the chick embryo. However, a role for the LECT2 gene product in the bursal microenvironment is unknown at present. The goal for this research project was to validate the expression of the LECT2 gene at the mRNA and protein level in the chick embryo bursa. Materials and Methods: The LECT2 gene transcript levels were determined by quantitative PCR with RNA derived from embryonic B-cells isolated at two different periods of bursal development. Whole protein extracts from the embryonic bursa were evaluated by mass spectrometry. Results: Expression of the LECT2 gene is significantly higher in B-cells from the early stage of bursal development. Mass spectrometry analysis revealed 9 different peptides from the LECT2 protein in the same embryonic period. Conclusion: The LECT2 gene is expressed at both the mRNA and protein level in the early period of bursa development. We postulate that LECT2 may contribute to B-cell migration into microenvironments established by non-lymphoid cells.